Adaptaciones Curriculares en Trastorno del Espectro Autista en estudiantes de preparatoria de la Escuela de Educación Básica Particular Miguel Ángel Suárez, 2023-2024 - Pucha Carrera, Evelyn Nicole (2024)
Autism spectrum disorder has a neurological basis and affects several areas of human development, i.e. it is a condition associated with social, cognitive, emotional and communication difficulties or impairments. In the present curricular integration paper, the objective was to analyse the curricular adaptations in the Autism Spectrum Disorder in high school students from the Escuela de Educación Básica Particular Miguel Ángel Suárez, 2023- 2024; it was a qualitative study, of descriptive type and non-experimental design. The sample population comprised 36 people, from which 1 is a teacher and 2 high school students diagnosed with autism. The data collection instruments used were a six-question interview, and a six-item observation sheet, from which, the following results were obtained: the characteristics of the curricular adaptations identified were the flexibility to adjust the students' activities. However, a limited application of the characteristics of inclusivity and integration was evident. The diagnostic elements of autism spectrum disorder that were described in the students were: difficulties in communication, hand mania and scattered gaze, which demonstrates a lack of in- depth knowledge of them by the teachers. Finally, an intervention proposal was elaborated, so that teachers have pedagogical strategies to implement in their curricular adaptations. It is concluded that, although there are curricular adaptations within the curriculum, these are not adequately implemented to support students with ASD, so that equitable access to quality education and the comprehensive development of students is not guaranteed.